A survey of homozygous deletions in human cancer genomes - Cox, Charles (National Academy of Sciences, 2005)
Homozygous deletions of recessive cancer genes and fragile sites are known to occur in human cancers. We identified 281 homozygous deletions in 636 cancer cell lines. Of these deletions, 86 were homozygous deletions of known recessive cancer genes, 17 were of sequenced common fragile sites, and 178 were in genomic regions that do not overlap known recessive oncogenes or fragile sites (“unexplained” homozygous deletions). Some cancer cell lines have multiple homozygous deletions whereas others have none, suggesting intrinsic variation in the tendency to develop this type of genetic abnormality (P < 0.001). The 178 unexplained homozygous deletions clustered into 131 genomic regions, 27 of which exhibit homozygous deletions in more than one cancer cell line. This degree of clustering indicates that the genomic positions of the unexplained homozygous deletions are not randomly determined (P < 0.001). Many homozygous deletions, including those that are in multiple clusters, do not overlap known genes and appear to be in intergenic DNA. Therefore, to elucidate further the pathogenesis of homozygous deletions in cancer, we investigated the genome landscape within unexplained homozygous deletions. The gene count within homozygous deletions is low compared with the rest of the genome. There are also fewer short interspersed nuclear elements (SINEs), long interspersed nuclear elements (LINEs), and low-copy-number repeats (LCRs). However, DNA within homozygous deletions has higher flexibility. These features may signal the presence of currently unrecognized zones of susceptibility to DNA rearrangement. They may also reflect a tendency to reduce the adverse effects of homozygous deletions by minimizing the number of genes removed.